Distribution of an increasing roe deer population in a fragmented Mediterranean landscape - Tellería, José Luis; Virgós, Emilio (Ecography, 1997)
This paper describes roe deer Capreolus capreolus distribution in central Spain, where the species has spread from the mountains into peripheral agricultural areas In this region, it is more abundant in forest fragments near the mountains than in those further away, in pine and oak woodlands than in sclerophyllous forests, and in forests with open water than in those lacking this resource The paper also analyzes whether habitat quality and geographic location of forests with respect to roe deer source areas are the two basic causes of its distribution, as predicted by some models of the species distribution in fragmented landscapes The results corroborate this hypothesis revealing that roe deer abundance is linked negatively to sclerophyllous forest cover and distance from mountains We conclude that this type of farmland seems to be sub-optimal for roe deer in comparison with forested, moist mountains
Keywords: abundance; Distribution patterns; forest cover; habitat quality (voyant); roe deer

Distribution of an increasing roe deer population in a fragmented Mediterranean landscape - Tellería, José Luis; Virgós, Emilio (Ecography, 1997)
This paper describes roe deer Capreolus capreolus distribution in central Spain, where the species has spread from the mountains into peripheral agricultural areas In this region, it is more abundant in forest fragments near the mountains than in those further away, in pine and oak woodlands than in sclerophyllous forests, and in forests with open water than in those lacking this resource The paper also analyzes whether habitat quality and geographic location of forests with respect to roe deer source areas are the two basic causes of its distribution, as predicted by some models of the species distribution in fragmented landscapes The results corroborate this hypothesis revealing that roe deer abundance is linked negatively to sclerophyllous forest cover and distance from mountains We conclude that this type of farmland seems to be sub-optimal for roe deer in comparison with forested, moist mountains
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: abundance; Distribution patterns; forest cover; habitat quality (voyant); roe deer

Seasonal and interannual occupation of a forest archipelago by insectivorous passerines - Tellería, J L; Santos, T (OIKOS, 1997)
The distribution of insectivorous passerines was studied in 31 fragments (0.1 to 350 ha) of a helm oak (Quercus ilex) Mediterranean forest archipelago in central Spain for two consecutive springs and winters (1988 to 1990). The study aimed to assess the role of forest size, abundance and other biological traits (nesting site and foraging substrata) of the species in their ability to occupy the fragments. The number of fragments occupied by the species (f(i)) was correlated to their abundance (d(i)) in spring and winter. Spring-to-winter changes of di correlated positively to changes off, due to the incidence of summer migrants but failed to show any significant pattern when restricted to species occurring in both seasons. The between-winter variations of cl, correlated positively with changes in f, while the between-spring changes of both parameters did not correlate, probably because of stronger effects of site fidelity on bird distribution in this period. Between-year persistence in the occupation of fragments was directly related to bird species abundance and, for a given abundance, persistence decreased in the smallest fragments. Hole-nesting species during the 1988 spring and the exploiters of scarce trees or foraging substrata during both winters showed an apparent restriction to colonize the smaller fragments due in parr to changes in habitat structure related to fragmentation. These results support the hypothesis that abundance is a good predictor of the ability of species to occupy and persist in fragments. However, abundance alone does not fully explain the processes that determine these occupancy patterns, since other traits related to the spatial scale of analysis and the suitability of fragments for each bird species are also involved.
APS
Keywords: abundance; biological traits; bird distribution; forest size; Holm oak; insectivorous passerines; mediterranean forest; Quercus ilex